Multisensory-Based Rehabilitation Approach: Translational Insights from Animal Models to Early Intervention - Purpura, Giulia; Cioni, Giovanni; Tinelli, Francesca (Frontiers in Neuroscience, 2017)
Multisensory processes permit combinations of several inputs, coming from different sensory systems, allowing for a coherent representation of biological events and facilitating adaptation to environment. For these reasons, their application in neurological and neuropsychological rehabilitation has been enhanced in the last decades. Recent studies on animals and human models have indicated that, on one hand multisensory integration matures gradually during post-natal life and development is closely linked to environment and experience and, on the other hand, that modality-specific information seems to do not benefit by redundancy across multiple sense modalities and is more readily perceived in unimodal than in multimodal stimulation. In this review, multisensory process development is analyzed, highlighting clinical effects in animal and human models of its manipulation for rehabilitation of sensory disorders. In addition, new methods of early intervention based on multisensory-based rehabilitation approach and their applications on different infant populations at risk of neurodevelopmental disabilities are discussed.